Optimalisasi Pembelajaran Baca Tulis Al Qur’an Berbasis Digital Interaktif di Mts PSM Randublatung Kabupaten Blora - Konik Fauziyah; Abdul Mufid; Moh Imam Mudhi Al Ghofiqi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to determine the optimization of interactive digital-based learning to read and write the Qur'an at MTs PSM Randublatung Blora, along with its supporting and inhibiting factors. This study uses a descriptive qualitative method with a case study type. Data collection methods use observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and conclusion drawing. Data validity tests consist of credibility tests, transferability tests, dependability tests, and confirmability tests. The results of the study indicate that the use of interactive digital media can optimize learning to read and write the Qur'an through several aspects, namely increasing learning motivation, student activeness in learning, making it easier for students to learn to read and write the Qur'an, and making it easier for teachers to deliver learning materials. This is supported by the availability of digital devices, teacher competence, and the learning environment. However, obstacles faced are limited facilities and technological skills that still need to be improved. The conclusion in this study is that the use of interactive digital media can optimize learning to read and write the Qur'an at MTs PSM Randublatung.